EVALUATION OF CASSAVA CHIPS DRAINING, FINAL PRODUCT HANDLING, AND PACKAGING IN CASSAVA CHIP “OJO LALI”, LAMPUNG TIMUR - Yuliana Sari; Wahidah Mahanani Rahayu (Jurnal Pangan dan Agroindustri, 2022)
Lampung is one of main cassava producer in Indonesia. One of its popular products is cassava chips, produced by many small enterprises with manual draining, product handling, and packaging. The purpose of this study was to analyze the evaluation of the handling cassava chips final product and to evaluate the packaging process of cassava chips based on package material used in Cassava Chip “Ojo Lali” East Lampung. Evaluation was conducted through direct observation on processing, packaging, and quantification of drained cooking oil. The result of this study showed that final product handling of cassava was not optimal indicated by low drained oil. Cassava chips were packed manually in polypropylene plastic by employees whom some of them were not careful, causing defect on most of the chips. Utilization of stapler to seal the packages need to be replaced for its potential hazard for consumers.